The Right to Speak Minang: A Constitutional Analysis of Indigenous Language Protection in Indonesia - Handoko, Handoko; Kaur, Sheena; Lau, Su Kia (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2026)
This paper aims to analyse the legal recognition and status of the Minangkabau language as an indigenous language in Indonesia, particularly in West Sumatra. The research focuses on doctrinal legal analysis and draws on socio-legal and comparative legal approaches to national and regional legislation, including the 1945 Constitution, Law No. 23/2014, Perpres No. 63/2019, Permendikbudristek No. 13/2022, and regional regulations. The research results show that although regional languages are recognised in the Indonesian legal system, they remain symbolic. The preservation of regional languages has not been explicitly included in the national legal system. Specifically for the Minangkabau language, language preservation at the school level still relies on the local content Keminangkabauan, which focuses more on introducing Minangkabau culture. Several regions in West Sumatra also have enacted local regulations that mandate the inclusion of local content in the Minangkabau language and literature. However, since regional language preservation policies are not regulated by a higher constitutional system, their implementation is often hampered by budgetary and resource constraints. Model language policies in Canada, New Zealand and South Africa provide valuable guidance for articulating policy measures that facilitate rather than frustrate efforts to revitalise and preserve indigenous languages. The research argues that Indonesia must develop an accessible, action-oriented legal framework for public policy development (beyond symbolic recognition) to ensure that indigenous languages, including Minangkabau, are maintained and promoted through education, media, and public life. This study provides policy-oriented solutions to enhance linguistic justice and protect indigenous languages across countries.